2010
DOI: 10.1159/000318172
|View full text |Cite
|
Sign up to set email alerts
|

Association of RS2200733 but Not RS10033464 on 4q25 with Atrial Fibrillation Based on the Recessive Model in a Taiwanese Population

Abstract: Objectives: To determine the association between genetic variants on chromosome 4q25 and atrial fibrillation (AF) in a Taiwanese population. Methods: We enrolled 200 patients with AF (mean age: 67 ± 13 years) and 158 controls (mean age: 63 ± 10 years). The genotypes of five SNPs, RS2634073, RS2200733, RS13143308, RS2220427 and RS10033464, were determined using multiplex single base extension methods. Results: The distribution of the RS2200733 and RS10033464 genotypes did not significantly deviate from the Hard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
(31 reference statements)
2
10
0
4
Order By: Relevance
“…The genes most closely linked to these risk variants are KCNN3, PRRX1, PITX2, WNT8A, CAV1, C9orf3, SYNE2, HCN4 and ZFHX3 2–4. Among them, variants near the PITX2 gene show the strongest association with AF; an association that has been independently replicated in other ethnic populations, including our Taiwanese population 5. An association of KCNN3 with AF was also found in our Taiwanese population 6.…”
Section: Introductionsupporting
confidence: 80%
“…The genes most closely linked to these risk variants are KCNN3, PRRX1, PITX2, WNT8A, CAV1, C9orf3, SYNE2, HCN4 and ZFHX3 2–4. Among them, variants near the PITX2 gene show the strongest association with AF; an association that has been independently replicated in other ethnic populations, including our Taiwanese population 5. An association of KCNN3 with AF was also found in our Taiwanese population 6.…”
Section: Introductionsupporting
confidence: 80%
“…(5) Subsequent studies have found a strong association for rs2200733 than for rs10033464. (6) (7) (8) Two additional SNPs on chromosomes 1q21 and 16q22 with modest effects have also been identified. (9) (10)…”
mentioning
confidence: 99%
“…In addition, Lee et al examined the genotypes of Wve singlenucleotide polymorphisms (SNPs), rs2634073, rs2200733, rs13143308, rs2220427 and rs10033464 in a Taiwanese population composed of 200 AF patients and 158 healthy controls using multiplex single base extension methods. They conWrmed the association between rs2200733 and AF, but failed to conWrm the association between rs10033464 and AF (Lee et al 2010). In sum, these studies consistently showed the association between rs2200733 and AF but not with rs10033464.…”
Section: Common Variants On 4q25mentioning
confidence: 98%